2019
DOI: 10.1186/s12891-019-2763-1
|View full text |Cite
|
Sign up to set email alerts
|

Open versus minimally invasive percutaneous surgery for surgical treatment of thoracolumbar spine fractures- a multicenter randomized controlled trial: study protocol

Abstract: Background Thoracolumbar fractures are most frequent along the spine, and surgical treatment is indicated for unstable fractures. Percutaneous minimally invasive surgery was introduced to reduce the pain associated with the open posterior approach and reduce the morbidity of the procedure by avoiding damage and dissection of the paravertebral muscles. The goal of this study is to compare the surgical treatment of fractures of the thoracolumbar spine treated by the conventional open approach and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Currently, posterior pedicle screw fixation is the most widely used method in clinical practice. Numerous clinical studies have shown that this method can immediately restore normal spinal sequence reconstruction and maintain spinal stability (9). However, this traditional surgical method also has significant disadvantages such as the method for patients with traumatic big, long operation time, intraoperative blood loss, and longer duration of postoperative pain in patients with incision, generally required long-term postoperative incision drainage tube, leading to stay in bed longer hospitalization and recovery.…”
Section: Original Articlementioning
confidence: 99%
“…Currently, posterior pedicle screw fixation is the most widely used method in clinical practice. Numerous clinical studies have shown that this method can immediately restore normal spinal sequence reconstruction and maintain spinal stability (9). However, this traditional surgical method also has significant disadvantages such as the method for patients with traumatic big, long operation time, intraoperative blood loss, and longer duration of postoperative pain in patients with incision, generally required long-term postoperative incision drainage tube, leading to stay in bed longer hospitalization and recovery.…”
Section: Original Articlementioning
confidence: 99%
“…The progress of surgical techniques in these indications has evolved considerably with the development of percutaneous surgery. Several studies have shown that the minimally invasive percutaneous procedure results in less damage to the paraspinal muscles, minimized blood loss, and reduced operating time, with almost similar results in terms of stabilization [18][19][20]. The advent of these techniques also makes it possible to offer surgical solutions to older patients who did not have access to them before.…”
Section: Discussionmentioning
confidence: 99%
“…However, the traditional procedure has disadvantages of long operative time, large blood loss, posterior ligaments complex injury, high infection rate, and persistent postoperative low back pain, which significantly affect the patient's quality of life. 9 With the development of minimally invasive concepts and minimally invasive surgery, percutaneous pedicle screw has various advantages, including less trauma, less bleeding, short operation time, and quick recovery. 10 It is an ideal method for patients suffering from thoracolumbar burst fracture with mild or without obvious lower-extremity neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%